A educação para além da ditadura estética: uma reflexão sobre indústria cultural e emancipação - Krette Júnior, Wilson (2013)
Education is a social and political practice characterized by the need of asking questions concerning learning processes and training of individuals in search of theoretical and practical improvement. Education is not a given truth, but a field in process, a field to be, that will always imply its self-questioning. Therefore, the self-understanding of education in a process of necessary self-referentiality is at stake. The context in which this dissertation arises is marked by the tension between a point of view that regards education as "emancipation" and, on the other hand, society, which does not foster the accomplishment of the project. In this sense, the concept of "Aesthetic Dictatorship" emerges as the expression able to offer a reading of the oppressive state of society, while the theme of education as emancipation arises as a proposal for a process to oppose to the general state of things. The theme of the death of subjectivity, of the mechanisms of annihilation of the subject of education, be it a teacher or student, is considered from the point of view of understanding a context which is aesthetically "totalitarian", by avoiding the individual to have the thought experiment ¬ that even being tragic, may be able to promote an exit from oppression. The concept of Aesthetic Dictatorship results mainly from an analysis of the text about the Cultural Industry, by Adorno and Horkheimer, published in the 1940’s. The reading of the text shows that the condition of the experience in general in society, is dominated by technology and by capital. Such condition, called by the authors as the Cultural Industry, takes place in our days as a silent and, at the same time, Aesthetic Dictatorship imperative. The text presented in this research seeks to unveil the characteristics of the totalitarian state of an aesthetic scheme – which is also ethical and political. Such unveiling obliges us to disclose a reflection about the meaning of the formation of the subject of education, be it the teacher, the student, or the individual who is living the social experience. In conclusion, what is proposed here is the reflection on what education can be, as well as its limits and potentials, in the era of the Aesthetic Dictatorship of the mass media.